A flexible RF energy harvester using a hybrid printing technology for 'stand-alone' wireless sensor platforms. (31st January 2018) - Kim, Sangkil; Jeong, Soyeon; Bito, Jo; Georgiadis, Apostolos; Tentzeris, Manos M
Abstract: A flexible RF energy harvester using a novel hybrid printing technology on low-cost polymer substrates is introduced in this paper. The presented printing technology is a hybrid approach taking advantage of the low-cost flexible printing and of the high-performance surface mounting technology. The design guidelines for the hybrid printed electronics, PdCl2 catalyst ink for inkjet-printing, and material characterization method using a ring resonator are discussed in detail. A flexible RF energy harvester is designed and its performance is experimentally verified for proof-of-concept purposes. The fabricated prototype generates more than 2.9 V when it is exposed to a power density around 1 μ W cm −2 at UHF radio frequency identification frequency range, demonstrating the feasibility and capability of the presented technology towards scalable conformal autonomous low-cost electronics.